Badan Perwakilan Desa: Harapan Bagi Pembaharuan Desa - S. Djuni Prihatin; Hempri Suyatna (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2001)
A stepforward in institutiorzalising democratic governance at the grass-roots level has been marked with the establishment of village representative body (Badan Perwakilan Desa, known as BPD). This article spells out various expectation embedded within such initiatives and assesses how the BPD lead to a more comprehensizie political reform at a grass roots level in Indonesia.